Analysis of pigment cell differences and carotenoid content in the skin of golden turbot (Scophthalmus maximus) with color variation - Zhifeng Liu; Mingchao Yang; Yuelei Shi; Pengfei Yan; Zhibin Sun; Junlian Zhong; Zhihui Huang; Hui Wang; Aijun Ma (Aquaculture Reports)
Golden-colored mutants of turbot (Scophthalmus maximus) have recently been identified in aquaculture, presenting a unique opportunity to study the underlying mechanisms of this rare coloration. This study investigated the differences in skin pigment cells and carotenoid metabolism between golden and normally pigmented turbot. Microscopic and histological analyses revealed that the skin of the control group contained both melanophores and xanthophores, with melanophores exhibiting fully extended dendrites and larger cell volumes, while xanthophores were smaller and dispersed among the melanophores. In contrast, the skin of the golden mutants also contained both melanophores and xanthophores; however, the melanophores were mostly rounded with less extended dendrites and reduced cell volumes, alongside an increase in both the number and size of xanthophores. Additionally, qPCR analysis of the BCL-2 and caspase gene families found no significant differences in the expression levels of selected genes in the skin tissues of turbot with different body colors, suggesting that the color changes in golden mutants are not due to apoptosis of pigment cells. Liquid Chromatograph-Mass Spectrometer (LC-MS/MS) analysis of carotenoid content showed an upregulation of specific carotenoids in the golden mutants, such as ε-carotene and zeaxanthin derivatives. These findings indicate that the golden coloration in turbot is primarily driven by changes in pigment cell composition and carotenoid accumulation. This study provides foundational insights into the genetic and metabolic pathways involved in fish coloration, with significant implications for selective breeding programs in aquaculture.